(untitled) (Journal of Shaheed Suhrawardy Medical College, 2020)
Objective: This study was undertaken with the aim to detect extent of drugs use in elderly patients at Cardiology outpatient department of a tertiary care teaching hospital and to evaluate inappropriate prescribing with the help of Beers Criteria 2015. Material and Methods: The study was carried out at Cardiology outpatient department of Shaheed Suhrawardy medical college hospital, Dhaka, Bangladesh from May 2018 to April 2019. Total 2351 Geriatric patients were included during the study period of 12 months. The data was collected in a prescribed data form which included the patient’s details and the prescriptions. Results: The result revealed that 11.96% of total drugs were prescribed inappropriate manner and 27.26% of total patients received at least one inappropriate drug prescription. Administration of a drug which should be avoided in elderly forms a common category of inappropriate drug use. Antihypertensive, Anti-platelets, Anti-diabetics, Antibiotics and Sedatives/ Hypnotics were the most common drug groups prescribed in inappropriate manner. Conclusion: This study shows high prevalence of inappropriate use of drugs in geriatric patients which needs attention to improve the situation. J Shaheed Suhrawardy Med Coll, December 2019, Vol.11(2); 101-105